PENGARUH STORE ATMOSPHERE, PRODUCT ASSORTMENT DAN HARGA TERHADAP MINAT BELI PADA TRANSMART CARREFOUR BUAH BATU BANDUNG - Rakhmawati, Rinrin Karina; Trenggana, Arlin Ferlina Mochamad (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2018)
Abstract Transmart Carrefour Buah Batu Bandung is one of Transmart Carrefour branches which has a modern store atmosphere strategy, the assortment and availability of products with the appropriate price. Transmart Carrefour Buah Batu Bandung trying to increase consumer purchase intention. Visitors has another purpose than shopping that creates lack of interest in purchasing. This research aims to analyze store atmosphere, product assortment and price towards purchase intention in Transmart Carrefour Buah Batu Bandung and its influence. Variables in this research consist of independent variable store atmosphere, product assortment and price. Dependent variable in this research is purchase intention. The method uses quantitative with descriptive verification type. Sampling with non-probability sampling technique and accidental sampling type. The population is 1,605 people and the sample is 100 respondents. This research used descriptive analysis and multiple linear regression. Descriptive analysis showed that all variables obtained good category. The results of regression analysis, and coefficient of determination, it can be concluded that store atmosphere, product assortment and price has a significant effect on purchase intention of 42,7%. Hypothesis test shows that three variables has a significant effect on purchase intention simultaneously and only store atmosphere that partially doesn’t have a significant effect on purchase intention. Keywords: Purchase Intention, Product Assortment, Store Atmosphere